The Regularity of Historic Development and Human Agency: Separate in Nature, United in the Combined Action of Human Beings (Asian Journal of Social Science Studies, 2022)
The relationship between the regularity of historic development and human agency varies with the formation and development of regularity: regularity emerges from the exercise of agency and then both constrains and guides the latter; the exercise of the agency determines the formation of regularity, and after its formation is constrained but actively uses it and strives for the initiative. The two are separated by their fundamental nature but are united twice by the combined action of human beings and the interaction of 'constraint' and 'use and strive for initiative'.